Aboveground carbon stocks and sequestration rates of forests under different management regimes in Churia region of Nepal - Subedi, Bipana; Lamichhane, Prakash; Magar, Lilu Kumari; Subedi, Thakur (Banko Janakari, 2022)
The impact of forest management activities on the ability of forest ecosystems to sequester and store atmospheric carbon is of increasing scientific and social concern. This research estimated the aboveground carbon stocks and carbon sequestration rates of forests under various management regimes in the Churia region of Nepal. We used tree data from 469 permanent sample plots distributed across the region from the data archive of Forest Research and Training Centre for the study. The data from 2012 and 2017 were used. The volumes of individual trees were calculated using species–specific allometric equations, which were then converted to biomasses using their respective wood densities. The carbon content was calculated by multiplying the biomass by 0.47 and was converted to the amount of sequestrated CO2 by multiplying by 3.67. We found that the average estimated aboveground carbon stock increased from 78.43 t ha–1 in 2012 to 89.20 t ha–1 in 2017, resulting in an average annual carbon sequestration rate of 5.34 t ha–1 yr–1 (i.e. 7.90 t CO2 ha–1 yr–1). The results showed significant differences in aboveground carbon stocks and annual carbon sequestration rates among different forest management regimes in the region. Generally, aboveground carbon stock was found to be the highest in protected areas in both years whereas, the annual carbon sequestration rate was found to be the highest in government–managed forests. It can be concluded that the Churia region has great potential in terms of carbon sequestration. The evidence of the strong association of carbon stock and sequestration rate with management regimes provides valuable information for policymakers to maintain and further enhance carbon storage in a geographically vulnerable region like Churia.